The Relationship between the Stock Exchange of Thailand and Other Assets, Before and During the Covid-19 Crisis - Ta-aituek, Chaiyanon; Srisuksai, Pithak; Adithipyangkul, Pudinan (Modern Management Frontier Journal, 2024)
The objective of this study is to analyze and compare the results before and during the COVID-19 crisis in three topics: 1) The causal relationship between the Stock Exchange of Thailand (SET) and other assets. 2) The effects of Volatility Spillover from other assets transmitting to the Stock Exchange of Thailand. 3) The Long-term relationship between the Stock Exchange of Thailand and other assets. The key results show that, during the crisis: 1) foreign equities, gold, and Thai bond index significantly Granger-cause the SET. 2) The Dow Jones Index, FTSE Index, and crude oil can transmit volatility to SET 3) The Dow Jones Index, FTSE Index, Nikkei Index, crude oil, Bitcoin, and Thai bond index exhibit a long-term relationship with SET